2013
DOI: 10.1209/0295-5075/101/34003
|View full text |Cite
|
Sign up to set email alerts
|

Vortexons in axisymmetric Poiseuille pipe flows

Abstract: Abstract. We present a study on the nonlinear dynamics of small long-wave disturbances to the laminar state in non-rotating axisymmetric Poiseuille pipe flows. At high Reynolds numbers, the associated Navier-Stokes equations can be reduced to a set of coupled Korteweg-de Vries-type (KdV) equations that support inviscid and smooth travelling waves numerically computed using the Petviashvili method. In physical space they correspond to localized toroidal vortices concentrated near the pipe boundaries (wall vorte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…This is the mechanism of inverse cascade of cross-stream vorticity in channel flows identified by Eyink (2008). Similar dynamics is also observed for long-wave disturbances associated to the KdV equations (4.2) (Fedele & Dutykh 2013).…”
Section: Vortexon Slugssupporting
confidence: 67%
“…This is the mechanism of inverse cascade of cross-stream vorticity in channel flows identified by Eyink (2008). Similar dynamics is also observed for long-wave disturbances associated to the KdV equations (4.2) (Fedele & Dutykh 2013).…”
Section: Vortexon Slugssupporting
confidence: 67%
“…The observed deviations from Taylor’s hypothesis appear to be the signature of the dispersive nature of turbulence. Moreover, the observed wave dispersion fairly agrees with the theoretical dispersion predicted for axisymmetric flows 18 , 19 , 21 .…”
Section: Discussionsupporting
confidence: 83%
“…Fedele and Dutykh 18 , 19 investigated the dynamics of non-rotating axisymmetric pipe flows in terms of nonlinear soliton bearing equations. They showed that at high Reynolds numbers, the dynamics of perturbations to the laminar flow obey a coupled system of nonlinear Camassa–Holm (CH) equations 20 .…”
Section: Wave Dispersion In Axisymmetric Navier–stokes Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the KdV and BBM-type equations appear in many other physical settings as well (see e.g. [11,17,18,20,30]).…”
Section: Perspectivesmentioning
confidence: 99%